2014 Electricity Profiles - United Nations Department of Economic; Social Affairs (United Nations, 2017)
The 2014 Electricity Profiles publication provides an overall picture of the electricity sector of over 200 countries and areas on an internationally comparable basis, for the years 2009-2014. It displays detailed information on production, trade and consumption of electricity, on net installed capacity and thermal power plant inputs and efficiency relevant to each of these countries and areas. This is the third issue of Electricity Profiles as a stand-alone publication, replacing the previous series of Energy Balances and Electricity Profiles.